RANCANG BANGUN APLIKASI KLUB FUTSAL PADA ASOSIASI FUTSAL KABUPATEN PANDEGLANG - Waliadi Gunawan; Sutanto; Tb Maulana Yosep (FAKULTAS TEKNIK, 2022)
Information technology currently has a very important role in all fields and aspects of life, both in the world of business, politics, and the economy. This is because the company's or society's needs for information can be met with technological developments. Academies or futsal clubs that have been registered in the futsal association of Pandeglang Regency are as many as 12 academies or clubs. In the futsal association of Pandeglang district, there is still a lack of organizational management and the administration of the academy or futsal club has not been organized. SDLC (system development life cycle) software development methodology with the water model waterfall, where it describes a systematic and sequential approach to software development, starting with the specification of user requirements and then continuing through the stages of planning (planning), modeling (modeling), construction (construction), and delivery of the system to customers/users (deployment), ending with support for the complete software produced. The results obtained are the application of information systems at the futsal association of Pandeglang district which will make it easier to manage player data and league match result data. With the association website futsal will make it easier to provide information about Futsal management information regarding the Official Leagues by futsal activists in Pandeglang Regency. With the futsal association website, it can solve organizational management problems for each futsal academy and club in Pandeglang Regency. With the futsal association website, you can complete the administrative order of the Academy or Futsal Club in Pandeglang Regency